Harnessing Nanomaterials for Advanced Electrical Components and Efficient Transformers - Tirgar Pravin; Mounica Patil; Kansal Lavish; Prashanth Kumar Sunil; Murugan A.S.S.; Ragunath N. (E3S Web of Conferences)
The advancements that have been made in nanotechnology and nanoscience have produced remarkable outcomes in the present day. As a result, they have found more uses in a wider range of fields, such as technology, physics, chemistry, and biology.These traditional ideas have been rendered obsolete as a result of the emergence of nanotechnology. The extraordinary performance of nanotechnology drew the attention of electrical engineers, who were interested in developing components for electrical systems that were dependable and efficient. By using the nanotechnology idea, electrical engineers are able to create nano-structured value-added goods that possess high superior features. This paper brings to a head the notion of nanotechnology in a variety of electrical components, including nanowires, insulators, transformers, and dielectric fluids, as well as prospective future possibilities.